Care providers' and patients' attitudes toward using electronic-patient reported outcomes to support patients with traumatic brain injury: a qualitative study (PRiORiTy). (11th May 2020) - McMullan, Christel; Retzer, Ameeta; Slade, Anita; Kyte, Derek; Jones, Laura; Belli, Antonio; Calvert, Melanie; Turner, Grace M.
ABSTRACT: Objectives: To (a) identify residual symptoms and deficits resulting from a traumatic brain injury (TBI) and impact on patients' and their families' quality of life; (b) explore views and experience of care providers, researchers, patients, and carers of using PROMs; and (c) explore their attitudes toward reporting symptoms and impacts on an electronic platform. Methods: Qualitative semi-structured interviews with people with TBI and their carers; health-care professionals, researchers, and third sector staff members working with people with TBI. Results: Symptoms and long-term impacts of TBI included cognitive problems, difficulties functioning, anxiety, and depression. PROMs were seen as improving knowledge of residual symptoms and their impact post-TBI but not always accurately reflecting patients' residual problems. Challenges to completing PROMs were cognitive impairment and lack of insight into condition. Perceived advantages of an electronic platform included easy data collection; flexibility; improving workflow; and the ability to send/ receive feedback and reminders easily. Suggested features of an electronic platform included simple layout, lay language, short questions, few items on the screen, and capability to send/receive feedback and additional information. Conclusion: There is a demand for reporting symptoms and their impact electronically, providing the layout is kept simple and feedback from clinicians is provided.